Pengaruh Kedalaman Pin (Depth Plunge) Terhadap Kekuatan Sambungan Las Pada Pengelasan Adukan Gesek Sisi Ganda (Double Sided Friction Stir Welding) Aluminium Seri 5083 - Prasetya, Damas (2016)
Welding in the manufacturing industry has an important role in the process of joining metals. One method of welding metal is friction stir welding / friction stir welding (FSW). Friction stir welding method of welding is welding by utilizing the heat due to rotation of the tool that is rubbing against the parent material or workpiece. Friction stir welding method is generally used to connect the aluminum material. The purpose of this research was to determine the effect of the depth of immersion pin (depth plunge) to changes in physical and mechanical properties of friction stir weld double sides (double sided friction stir welding). This study was conducted using a vertical milling machine for material Al 5083 with the long dimension of 200 mm x width 100 mm x thickness of 3 mm by 6 specimens. The parameters used are rotational speed 1250 rpm spindle, feeding speed of 12.5 mm / min, immersion depth variation pin 0.9 mm, 1.9 mm and 2.9 mm. After the welding process is completed followed by tensile testing, testing micro vickers, macro image and a micro photograph. From the test results known to the highest tensile stress on variations plunge depth of 1.9 mm amounted to 177.78 Mpa. For testing micro vickers welding area decreased hardness when compared with the parent metal and HAZ region has the lowest hardness. While in the observation of the macro image of welding is plugged in, but it happens on a welding defect cavity with variations plunge depth of 2.9 mm. In observation of micro photograph happen diminution grain structure in the region stir zone.